2021
DOI: 10.1124/molpharm.121.000400
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulator KM822 Attenuates Behavioral Actions of Amphetamine in Caenorhabditis elegans through Interactions with the Dopamine Transporter DAT-1

Abstract: Aberrant dopamine (DA) signaling is associated with several psychiatric disorders such as autism, bipolar disorder, addiction, and Parkinson's disease, and several medications that target the DA transporter (DAT) can induce or treat these disorders. In addition, psychostimulants, such as cocaine and D-amphetamine (AMPH), rely on the competitive interactions with the transporter's substrate binding site to produce their rewarding effects. Agents that exhibit noncompetitive, allosteric modulation of DAT remain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…To test if Amph causes physiological changes during embryogenesis without the interference of possible effects from Amph-induced changes in maternal care, we used the simple model Caenorhabditis elegans (C. elegans). This model lacks maternal care but retains a conserved dopaminergic response to Amph [16,17]. In fact, previous data showed that when forced to swim in solutions containing 0.3-1 mM Amph, C. elegans exhibits a unique behavior named Swimming-Induced Paralysis (SWIP), and we demonstrated that Amph-induced SWIP is caused by an overload of DA in the synapses through DAT-1 reversal function.…”
Section: Introductionmentioning
confidence: 69%
“…To test if Amph causes physiological changes during embryogenesis without the interference of possible effects from Amph-induced changes in maternal care, we used the simple model Caenorhabditis elegans (C. elegans). This model lacks maternal care but retains a conserved dopaminergic response to Amph [16,17]. In fact, previous data showed that when forced to swim in solutions containing 0.3-1 mM Amph, C. elegans exhibits a unique behavior named Swimming-Induced Paralysis (SWIP), and we demonstrated that Amph-induced SWIP is caused by an overload of DA in the synapses through DAT-1 reversal function.…”
Section: Introductionmentioning
confidence: 69%
“…These knocked-out mice treated with cocaine displayed diminished behavioral cocaine responses [21]. But all known DAT modulators [22] or Vav2 antagonists are non-FDA-approved drugs. Interestingly, recent evidence highlighted that piRNAs induced by L-methionine down-regulate the Vav2 gene via a miRNA-like mechanism (Figure 1).…”
Section: Dopamine Transporter Hypothesismentioning
confidence: 99%
“…In an animal model, we demonstrated that the compound did not affect the locomotion of planarians but inhibited cocaine-induced hyperlocomotion. In a follow up study our group in collaboration with the Blakely group also demonstrated that KM822 attenuates an amphetamine-induced behavior in C. elegans roundworms and does not induce this behavior by itself ( Refai et al, 2022 ). Furthermore, we found that this did not occur in an animal with DAT genetically removed, supporting that this behavioral effect is elicited through the specific allosteric modulation of DAT function.…”
Section: Evidence Of Functional Impact Made By Allosteric Modulatorsmentioning
confidence: 99%